USING ‘MIME GAME’ TO TEACH VOCABULARY TO YOUNG LEARNERS - Mardhatillah Mardhatillah; Ratmanida Ratmanida (Journal of English Language Teaching, 2016)
In this paper, the author discusses the use of 'mime game' in teaching English vocabulary for young learners. To teach young learners, we must first understand their characteristics and needs. The fact is that young learners love to play. Therefore, learning through playing is the most appropriate way to teach them. One of them is to use the game called as "mime game". Teaching through "mime game" will be begun with classes will be formed into a half circle and then a student will be given a word. Furthermore, the chosen students will be in the middle class while giving expression by using gesture and the other students try to guess the word in question. Young learners are also very fond of moving and imagining. By using "mime game", young learners will get moved by using their own way and imagine to guess a certain word. Basically, young learners will easily remember what they learn when they feel happy, comfortable, love, and enjoy what they do.